Students’ character based on gender, grade, and school: religious, nationalism, integrity, independent and cooperative - Apriani, An-Nisa; Perdana, Riki; Harun, Harun; Sari, Indah Perdana; Wuryandani, Wury; Salim, Ahmad; Wahyudi, Andi; Riwayani, Riwayani (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aims to describe students’ character value and reveal the relationship of character values in elementary school children based on gender, grade and type of the school. The character values analyzed include religion, nationalism, integrity, independence, and cooperative values. This research was a quantitative method with a cross-sectional design by explaining and analyzing the results using Jeffrey’s amazing statistics program (JASP) software and students’ character values was categorized and described according to the aspect, gender, grade, and type of the school. Character of elementary school children (CESC) questionnaire was used as an instrument in this study. CESC have very good internal consistency (0.80 to 0.87) and have suitability construct model. The respondent of this study was 862 students obtained through the stratified random sampling randomly technique in elementary school at Yogyakarta Province. The result of this study confirmed that the students’ character value is a high level. The lowest aspect is integrity (2.40), while the highest aspect is religious (3.16). There is a relationship between the character values: religion, nationalism, integrity, independent, and cooperative values. It indicates that policymakers or teachers should improve students’ character value by training or applying a learning model that focuses explicitly on students’ character.